2016
DOI: 10.3390/ma9090717
|View full text |Cite
|
Sign up to set email alerts
|

New Rhenium-Doped SrCo1−xRexO3−δ Perovskites Performing as Cathodes in Solid Oxide Fuel Cells

Abstract: In the aim to stabilize novel three-dimensional perovskite oxides based upon SrCoO3−δ, we have designed and prepared SrCo1−xRexO3−δ phases (x = 0.05 and 0.10), successfully avoiding the competitive hexagonal 2H polytypes. Their performance as cathode materials in intermediate-temperature solid oxide fuel cells (IT-SOFC) has been investigated. The characterization of these oxides included X-ray (XRD) and in situ temperature-dependent neutron powder diffraction (NPD) experiments for x = 0.10. At room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
4
13
1
Order By: Relevance
“…A smaller overall polarization resistance of the x = 0.05 Ru-doped perovskite is observed compared to the x = 0.1 sample. At 850 °C, the 10% mol Ru-doped sample presents R p = 0.11 Ω cm 2 and the 5% mol Ru-doped R p = 0.07 Ω cm 2 ; this last sample exhibits extraordinarily low values, comparable to those of other cathodes with good performance such as SrCo 1– x Re x O 3−δ , SrCo 1– x V x O 3−δ , and SrCo 1– x Ti x O 3−δ . , …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…A smaller overall polarization resistance of the x = 0.05 Ru-doped perovskite is observed compared to the x = 0.1 sample. At 850 °C, the 10% mol Ru-doped sample presents R p = 0.11 Ω cm 2 and the 5% mol Ru-doped R p = 0.07 Ω cm 2 ; this last sample exhibits extraordinarily low values, comparable to those of other cathodes with good performance such as SrCo 1– x Re x O 3−δ , SrCo 1– x V x O 3−δ , and SrCo 1– x Ti x O 3−δ . , …”
Section: Resultsmentioning
confidence: 73%
“…All the reflections can be indexed at RT in a superstructure with doubled c -axis, as a = b ≈ a 0 , c ≈ 2 a 0 in the P 4 /mmm space group (No. 123), and the crystal structure was refined in a model derived for other doped-SrCoO 3‑δ oxides. In this model, Sr atoms are placed at 2 h (1/2,1/2, z ) sites, Co1 at 1 a (0,0,0), Co2 at 1 b (0,0,1/2), and the three kinds of oxygen atoms O1 at 2 f (1/2,0,0), O2 at 2 g (0,0, z ) and O3 at 2 e (1/2,0,1/2) positions. First, Ru atoms were placed together with Co1 resulting in a negative occupancy factor for Ru atoms, for that reason Ru atoms were distributed over the 1 b sites together with Co2 giving a reasonable occupancy factor for both Co and Ru atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While LaFeO 3 itself is not active, it provides high oxygen mobility and flexible redox character, properties which are instrumental in designing stable reforming catalyst [33]. The precursor materials reported in this study are LaFeO 3 (LF), LaNi [34][35][36]. The Re that did not enter the perovskite went to form the competing La 3 ReO 8 phase ultimately forming a composite precursor material.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the cubic phase exhibits an excellent ionic and electronic conductivity, the hexagonal phase has very poor properties and, unfortunately, it is thermodynamically stable, which limits the use of this pure material as a cathode in SOFC. As a strategy to prevent this cubic-to-hexagonal phase transition, it was found that replacing few percentages of Co by aliovalent elements like Re, Nb, Sb or Ti was effective to stabilize the cubic phase in a wide temperature range [9,10,11,12,13]. Recently, we observed that replacing 5% of Co by Ru prevents this unwanted transformation and enhances the catalytic oxygen reduction reaction [14].…”
Section: Introductionmentioning
confidence: 99%